Effects of Fibre-rich Ingredients at Different Levels on Growth Performance, Blood Parameters, and Carcass Yields of Broiler Chickens - Mulyantini, Ni Gusti Ayu; Suryatni, Ni Putu Febri (Jurnal Ilmu-Ilmu Peternakan, 2025)
This study aimed to analyse the effects of different sources of fibre-rich ingredients (FRI) at different levels on the growth performance, blood parameters, and carcass yields of broiler chickens. A total of 135 broiler chickens (21-day-old, mixed male and female) were allocated to 9 treatments consisting of 3 replicates with 5 chickens per replicate. The research methods used a completely randomized design with a 3x3 factorial pattern involving 3 types of FRI (rice bran (RB), wheat bran (WB), and corn bran (CB)) and 3 levels (L) of FRI (10%, 20%, 30%). Body weight gain (BWG), feed intake (FI), and FCR data were collected for the finisher (d 21?35) phase. The carcass and serum samples were analysed on day 35. There were no significant 2-way interactions for growth, carcass, or blood parameters. There was no difference in the growth performance of broilers fed RB, WB, or CB. The levels of FRI individually affect growth, carcass, and blood parameters. Compared with birds receiving 10% and 20% FRI, those receiving 30% FRI presented lower FI, BWG, and carcass yields. The highest measurement of total cholesterol (TC) occurred in broilers fed RB, and the lowest values of TC were obtained in those fed WB and CB. No differences were detected in triglycerides (P>0.05), but total serum HDL was significantly (P<0.05) greater in chickens fed WB and CB than in those fed RB. In conclusion, RB, WB, or CB can be used as a source of FRI for better growth performance, carcass, and blood parameters at moderate inclusion levels (10–20%) in broiler diets.